1968
DOI: 10.1177/001872086801000106
|View full text |Cite
|
Sign up to set email alerts
|

Improving Time-Sharing Performance of Pilots Through Training

Abstract: Even with special display devices in gestation, a pilot must satisfy his complete visual information needs by “time-sharing” between the intra- and extra-cockpit data sources. A sample of sixty military attack pilots, selected with the variable of flying experience in view, was divided into control and trainee groups. Using simple, generalized but adaptive simulation devices, the trainee group was trained over an eight-week period in display reading and in hazard detection. A comparison of the trainee group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This type of display, although Investigation has shown that the minimum time required to accommodate from outside the cockpit to the instrument panel, read an instrument, and then return to viewing the external scene is approximately 2. 5 seconds (Gabriel and Burrows, 1968). Such large time measures indicate that this transitioning constitutes a significant loss in the time available to the pilot for actually processing visual information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of display, although Investigation has shown that the minimum time required to accommodate from outside the cockpit to the instrument panel, read an instrument, and then return to viewing the external scene is approximately 2. 5 seconds (Gabriel and Burrows, 1968). Such large time measures indicate that this transitioning constitutes a significant loss in the time available to the pilot for actually processing visual information.…”
Section: Discussionmentioning
confidence: 99%
“…Time-sharing here refers to alternating attention between inside-the-cockpit information and external-scene information. Studies (Pfeiffer et al, 1963;Gabriel and Burrows, 1968) have shown that appropriate training can improve skill in time-sharing, scanning the outside scene, and hazard detection. However, such gains are limited to the extent to which they can be exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other experimental studies show evidence that training specific to task management improved cockpit multitasking performance (Gabriel & Burrows, 1968;Hoover & Russ-Eft, 2005;Premesalar, 1969).…”
Section: Training In Attention Workload and Task Managementmentioning
confidence: 98%
“…However, their study did not address longer term effects of the training. In a study conducted with U.S. Marine aviators (Gabriel & Burrows, 1968), pilots were trained to prioritize cockpit tasks and to acquire all necessary information from cockpit instruments before refocusing their attention outside. Pilots who had this training were much better at detecting external targets than those who were not trained, even several months after the training had occurred (Gabriel & Burrows, 1968), which indicates they were better able to divide their attention and resources as a result of specific training.…”
Section: Training In Attention Workload and Task Managementmentioning
confidence: 99%